Effect of Water Quality on Monthly Density Variation of the Endangered Southern Medicinal Leech Hirudo verbana Carena, 1820 (Hirudinea: Arhynchobdellida: Hirudinidae) - Saglam, Naim; Ozbay, Ozkan; Demir, Timur; Balci, Mustafa; Pala, Aysegul; Kilic, Ali (Inst Zoology, Bas, 2018)
The species of the genus Hirudo are threatened but still used worldwide in human treatment. We studied the density changes of southern medicinal leech Hirudo verbana and some water quality parameters monthly during a year in the Akpinar Marsh, Eastern Anatolia, Turkey. Samples of H. verbana were collected using a modified unit square design and unit time collecting method as an indicator for population density. Some water parameters such as water temperature, dissolved oxygen, pH, some cationic elements (lithium, sodium, ammonium, potassium, magnesium, calcium) and anionic elements (fluoride, chloride, sulphate, nitrate, phosphate, bromide) were determined. These parameters were analysed to detect their impact on population density of this medicinal leech. The populations of H. verbena were most dense in May-June; the species was found in smallest numbers in November and hibernating in December-March. A significant correlation (p<0.05) between the number of medicinal leeches in the unit area and monthly water temperature, amount of ammonium and fluoride was determined using the Pearson correlation coefficient. In the Akpinar Marsh, the largest adult medicinal leeches (>5 g) in the fourth size group formed 12.50-27.50% of the population and the smallest (<1.0 g) in the first size group formed 7.50-38.24%.
Keywords: Water quality; monthly variation; density; medicinal leech; Hirudoverbana